Traditional Wisdom of Adat Law Baduy Community In Farming System In Kanekes Village, Leuwihdamar Lebak Banten (Jurnal Cita Hukum, 2017)
Baduy community, tradition laws were a genealogical community with the type of lineage according to the male line (patrilineal). They believed in a descent or the same origin through the teachings of Sunda Wiwitan religion. The teachings of Sunda Wiwitan were the basis or guidance in their life. In terms of farming that they did was a mandate it religion that they professed or believed. Environmental wisdom in terms of farming with the system of shifting cultivation or dry rice (huma) was a mandate of the teachings of its religion. Masyarakat hukum adat Baduy merupakan komunitas masyarakat yang bersifat geneologis dengan tipe pertalian keturunan menurut garis laki-laki (patrilineal). Mereka mempercayai satu keturunan atau asal usul yang sama melalui ajaran agama Sunda Wiwitan. Ajaran agama Sunda Wiwitan ini merupakan dasar atau pedoman dalam kehidupan masyarakatnya. Dalam hal bercocok tanam yang mereka jalankan merupakan amanat agama Sunda Wiwitan yang mereka anut atau percayai. Kearifan lingkungan dalam hal bercocok tanam dengan sistem ladang berpindah atau sawah kering (huma) adalah amanah dari ajaran agama Sunda Wiwitan. DOI: 10.15408/jch.v5i1.5398